Sovereign risk – How can we measure it? - Černohorský, Jan; Pokorná, Kristýna; Teplý, Petr (Univerzita Pardubice, 2011)
This paper focuses on sovereign credit risk meaning a hot topic related to the current Eurozone crisis that started in early 2010. In the light of the recent financial crisis, market perception of the creditworthiness of individual sovereigns has changed significantly. Before the outbreak of the financial crisis, market participants did not differentiate between credit risk born by individual states despite different levels of public indebtedness. In the proceeding of the financial crisis, the market participants became aware of the worsening fiscal situation in the European countries and started to discriminate among government issuers. Concerns about the increasing sovereign risk were reflected in surging sovereign risk premium. The main aim of this paper is to shed light on the characteristics of the sovereign risk with the special attention paid to the mutual relation between credit spread and the CDS premium as the main measures of the sovereign risk premium.
Keywords: cointegration; credit default swap; credit risk; credit spread; sovereign risk